Cryptosporidium infection in ostriches (Struthio camelus) in Brazil: clinical, morphological and molecular studies - Santos, Mmab [UNESP]; Peiró, Jr [UNESP]; Meireles, Mv [UNESP] (Fundação APINCO de Ciência e Tecnologia Avícolas, 2005)
Avian cryptosporidiosis has been reported in more than 30 species of birds. To date, the species infecting birds are C. baileyi, C. galli and C. meleagridis. In this study, the morphological, clinical and molecular characteristics of a Brazilian ostrich isolate of Cryptosporidium are described. The oocysts of this Brazilian isolate are larger and more elongated than those of Cryptosporidium previously reported in ostriches, which were morphologically similar to C. meleagridis. Morphological, biological and molecular analyses demonstrated similarity of this ostrich isolate with C. baileyi, suggesting that there are at least two Cryptosporidium species infecting ostriches; one with molecular, biological and morphological characteristics related to C. baileyi, and another morphologically similar to C. meleagridis.
Keywords: Clinical signs; Cryptosporidium; morphology; ostriches; PCR-RFLP